PERSPECTIVE OF ISLAMIC EDUCATION TO VALUE CONTINUITY AND CULTURE - Musyarif, Ahdar, Abd. Halik, (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2020)
ABSTRACTEducation is a conscious and deliberate effort to create anatmosphere of learning and the learning process so that learners areactively developing the potential for him to have the spiritual strength ofreligious, self-control, personality, intelligence, noble character, and theskills needed themselves and society. Education continues throughout theages and absolutely mumust be carried out by each individual. Islamiceducation as an activity that can never be separated from personal andsocial life. Islamic education encourages people to maintain the existenceof Islamic normative values and positive cultural values. The article istalking about perspective of Islamic Education to contunity value andculture. The task of Islamic education is the development of potential,cultural inheritance, and interaction between culture and potential. Toachieve this, students must be fostered to become adults, that is, they havethe level of humanization, the level of homanization, the complete level,the internalization of values, and the level of self-reliance; while theFunction of Islamic Education is as an instrument of maintaining anddeveloping cultural values and community norms (Islam) and as a meansof making changes (innovation) through science and skills. Islamiceducation is essentially a process of cultural formation and transformation.The mission of Islamic education is internalization of cultural values intoeducational activities, education as a vehicle for the socialization ofcultural values, closing the space of contamination of negative globalcultural influences, and developing cultural values of work ethics. Thestrategy of Islamic education is learning orientation, flexible organization excellent service, and continuous and accommodating.